An integrated paradigm to understand the antibacterial and antifungal potential of bimetallic core-shell platinum silver (Pt@Ag) nanoparticles: A one health approach - Bamb, Aagam Lalit; Varma, Sanjana; Gade, Tejas Subhash; Palaskar, Shahaji; Vamkudoth, Koteswara Rao; Vyawahare, Niraj; Chaudhari, Pallavi M.; Chaudhari, Bhushan P. (Microbial Pathogenesis, 2025)
The concurrent occurrence of various microbial infections escalates the need to develop new treatments that can tackle multiple microbes and improve clinical outcomes. This study reports the synthesis and comprehensive evaluation of core-shell platinum-silver nanoparticles (Pt@AgNPs) designed to elucidate the antimicrobial effects while ensuring biocompatibility. The synthesis protocol was meticulously optimized to investigate the impact of precursor concentrations and reagent conditions. High-end characterization confirmed the formation of a welldefined core-shell structure with spherical morphology, crystalline nature, a face-centred cubic (FCC) lattice, high monodispersity, and stability, with a mean size of 20.344 +/- 4.492 nm. The antimicrobial potential of Pt@AgNPs was validated through a minimum inhibitory concentration (MIC) assay, revealing potent activity with MIC values of 15.6 mu g/mL for Pseudomonas aeruginosa and Staphylococcus aureus and 3.9 mu g/mL for Escherichia coli. Antibiofilm assay demonstrated significant inhibition of biofilm formation by P. aeruginosa at concentrations as low as 3.9 mu g/ml. The nanoparticles also exhibited notable antifungal activity, as indicated by an inhibition of 65.19 % for Aspergillus niger and 61.82 % for Fusarium verticillioides. Furthermore, hemocompatibility was noticed with the hemolysis assay, and the antioxidant properties of nanoparticles, assessed through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, underscored their potential to mitigate oxidative stress. This integrative study positions Pt@AgNPs as a promising platform for combating the occurrence of co-infections. The core-shell nanoparticle serves as a versatile tool in antimicrobial defence, exhibiting antibacterial, antifungal, antibiofilm, and antioxidant activity. Thus, it highlights their commercial translational potential as a next-generation antimicrobial intervention.
Keywords: Antibacterial; antibiofilm; antifungal; Antioxidant; Co-infections; Pt@Ag nanoparticles